ANALISIS KEPERCAYAAN DIRI SISWA KELAS III SEKOLAH DASAR - Liskar Antika Antika; Maharani Oktavia Oktavia; Puji Ayu Rachamawati (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2023)
Self-confidence is an attitude or feeling of confidence in one's abilities so that children are not too anxious in every action they take, students who have self- confidence tend to be more motivated to learn and develop their abilities, they tend to show better academic performance because they have confidence. that they can overcome challenges and achieve their goals, the formulation of the problem of this research is how to describe the self-confidence of grade III elementary school students. The aim of this research is to describe students' self-confidence in class III of elementary school. The research method used is descriptive qualitative, where this research is used to see a complete and complete picture of students' confident behavior. The results of the research concluded that the self- confidence of class III students at SD Negeri 140 Palembang can be said to be good, based on the data that has been collected there are 21 students out of 28 students in the good category, the majority of students are active when participating in the learning process and dare to express their opinions and The questionnaire data shows a percentage of 61.5%, where the results show that students' self-confidence is in the good category.Keywords : self-confidence, thematic Learning, student